DAMPAK LIMBAH DOMESTIK PERUMAHAN SKALA KECIL TERHADAP KUALITAS AIR EKOSISTEM PENERIMANYA DAN DAMPAKNYA TERHADAP KESEHATAN MASYARAKAT - Arif Sumantri; Muhammad Reza Cordova (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2011)
Increasing number of houses will increase in domestic waste. The high level of domestic pollution not only an impact on the waters, but also can affect the health quality of people that live along the banks of the river. The aims of this study are to determine the quality of domestic wastewater in arranged housing and the impact on river water quality. The research was conducted in August 2008 on a small scale housing Puri Nirwana Estate, Cibinong. We found domestic waste water from household activity in Puri Nirwana Estate were affecting recipient ecosystem (river). This river was polluted with indication the high value of COD, total coliform and content of detergent in the water, would endanger the health of local people who live in unplanned housing. Key words : Domestic waste water, Pollution, River, Puri Nirwana Estate, public health